A intencionalidade vital na obra "A estrutura do comportamento", de Merleau-Ponty - Marangoni, Pedro Henrique Santos Decanini [UNESP] (2017)
The aim of this study is to elucidate the foundations of a theory of living, or animal, intentionality, in the book "The Structure of Behavior", of Merleau-Ponty. We conducted an exegetical research of this book, taking into account the authors read by Merleau-Ponty and without neglecting the critic literature. This methodology has enabled us to undertake an interpretation of the analyzes performed by the philosopher around the living perception, having as axis the notion of intentionality, which was not explicitly used in his book. The use of the notion intentionality comes from Etienne Bimbenet's works. We show that since the beginning of the book, Merleau-Ponty is concerned to provide an active and significant status to the living experience. This concern goes through different phases. Initially, we highlight the author's dialogue with scientific psychology, especially with Pavlov's work, with the purpose to give more precise outlines to the idea of behavior. The criticism directed to reflexology resizes the role played by the organism as a passive agent, so that begins a series of arguments that form the basis for a theory of vital intentionality. The discussions about brain physiology send us directly to the problem of action. This question is worked in the second chapter, where we propose to discuss the problem of intentionality in the light of the concept of form. Through a structural description of behavior, Merleau-Ponty recognizes the originality and specificity of the vital order. Then, we treat the human perception and their differences in relation to animal perception through the concept of perspective multiplicity, created by Merleau-Ponty. At this point, the question of human's perception meaning is held under the background of animality. As a complement, we list some contemporary theoretical constructs belonging to philosophy and cognitive sciences that underpin or were directly influenced by the issues discussed in "The Structure of Behavior".